ANALISIS PENDAPATAN DAN PENDIDIKAN ORANG TUA DALAM USAHA PENURUNAN STUNTING (Studi Di Kecamatan Muara Sahung Kabupaten Kaur) - Hiriana, Hiriana (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
Stunting is a threat to the nation's next generation, because if stunting continues to increase it will affect the quality of human resources in the future. The increase and decrease in stunting is partly caused by parental income and parental education. Therefore, this research focuses on parental income and education as well as reducing stunting in the work area of the Kaur District Health Service. The aim of this research is to analyze parental income and parental education in an effort to reduce stunting. This research is a qualitative descriptive research. The number of informants used was 8 people. The research results show that a decrease in parental income can increase the risk of stunting and an increase in parental income can reduce the risk of stunting. Increasing parental education can reduce the risk of stunting and lack of parental education can increase stunting. Stunting in children in Muara Sahung and Sumber Makmur villages is caused by low and decreasing parental income and parents having less or less education.